ISLAMIC BUSINESS IN INDONESIA, MALAYSIA, AND UNITED KINGDOM (UK) - Ainun, Rania Nur; Santoso, Suryo Budi (Universitas Indo Global Mandiri Palembang, 2022)
When discussing the Islamic economic system, the direction cannot be separated from the sectors within it, specifically the Islamic finance region and the non-Islamic finance region. In this dialogue, we can speak about the prevailing Islamic commercial enterprise fashion in numerous nations. The cause of this look is to accumulate a few facts associated with sharia commercial enterprise in numerous nations that are predicted to assist folks who are traveling or who’re seeking out centers that can be according to sharia standards. The approach utilized in writing the item is a qualitative statistics series approach taken from a set of articles associated with sharia commercial enterprise in numerous nations. The results of this survey provide facts related to Shariah trading companies in countries such as Indonesia, Malaysia, and the United Kingdom. In summary, Islamic industrial enterprises exist in the majority of Islamic countries (Indonesia and Malaysia) in addition to the minority Islamic countries (including the United Kingdom). Islamic commercial enterprise became created on the idea of a country’s want to facilitate its citizen (For improving the Muslims of their own country) or for the diversity of Muslim travelers traveling the country.